2017
DOI: 10.4097/kjae.2017.70.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Dual antiplatelet therapy and non-cardiac surgery: evolving issues and anesthetic implications

Abstract: Dual antiplatelet therapy (DAPT) consisting of aspirin plus a P2Y12 inhibitor (clopidogrel, prasugrel, or ticagrelor) is imperative for the treatment of acute coronary syndrome, particularly during the re-endothelialization period after percutaneous coronary intervention (PCI). When patients undergo surgery during this period, the consequences of stent thrombosis are far more serious than those of bleeding complications, except in cases of intracranial surgery. The recommendations for perioperative DAPT have c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Derived from the cardiologists' practice for the management of stents in coronary diseases 3 , interventional neuroradiologists usually use dual antiplatelet therapy (aspirin plus a P2Y12 receptor inhibitor [clopidogrel, prasugrel or ticagrelor]) during the first weeks/months after stenting (with no consensus between the different teams around the world), and then switch for a single anti-platelet therapy (for a total of at least one year in our Institution). The drawback of this strategy is that most of the antiplatelet agents used in the field of interventional neuroradiology have a slow onset of action (2-8 hours for clopidogrel, for instance) 4 , thus requiring a loading dose before the endovascular treatment. Additionally, the long duration of platelet inhibition induced by P2Y12 inhibitors 4 is challenging for the management of hemorrhagic complications or unplanned high bleeding risk procedures, including ventricular drainage setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Derived from the cardiologists' practice for the management of stents in coronary diseases 3 , interventional neuroradiologists usually use dual antiplatelet therapy (aspirin plus a P2Y12 receptor inhibitor [clopidogrel, prasugrel or ticagrelor]) during the first weeks/months after stenting (with no consensus between the different teams around the world), and then switch for a single anti-platelet therapy (for a total of at least one year in our Institution). The drawback of this strategy is that most of the antiplatelet agents used in the field of interventional neuroradiology have a slow onset of action (2-8 hours for clopidogrel, for instance) 4 , thus requiring a loading dose before the endovascular treatment. Additionally, the long duration of platelet inhibition induced by P2Y12 inhibitors 4 is challenging for the management of hemorrhagic complications or unplanned high bleeding risk procedures, including ventricular drainage setting.…”
Section: Introductionmentioning
confidence: 99%
“…The drawback of this strategy is that most of the antiplatelet agents used in the field of interventional neuroradiology have a slow onset of action (2-8 hours for clopidogrel, for instance) 4 , thus requiring a loading dose before the endovascular treatment. Additionally, the long duration of platelet inhibition induced by P2Y12 inhibitors 4 is challenging for the management of hemorrhagic complications or unplanned high bleeding risk procedures, including ventricular drainage setting. Moreover, platelet inhibition induced by some antiplatelet agents, like ticagrelor, is difficult to neutralize, which may lead to dramatic complication in case of hemorrhage 5 .…”
Section: Introductionmentioning
confidence: 99%
“…This percentage increased to 30 to 50% with the use of dual antiplatelet therapy. 21,22 Our study is the pioneer work showing a general lack of medical awareness with regards to antiplatelet therapy and stents among patients who go through PCI. 23 The results from our study showed that only 15% of the total patients had an adequate level of awareness about stents and pharmacotherapy therapy after PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies assessed the perioperative bleeding risk in patients with APT undergoing non‐cardiac surgery . The prospective POISE‐2 trial reported an overall bleeding rate of 4.6% in nearly 5000 patients left on aspirin throughout elective non‐cardiac surgery .…”
Section: Discussionmentioning
confidence: 99%